Evaluation of a rapid susceptibility test of polymyxin B by MALDI-TOF - Barth, Patricia Orlandi; Volpato, Fabiana Caroline Zempulski; Moreira, Natália Kehl; Wink, Priscila Lamb; de Souza, Ândrea Celestino; Barth, Afonso Luís (Frontiers in Microbiology, 2022)
Introduction Infections caused by multidrug-resistant microorganisms have become increasingly common in hospital environments around the world. Gram-negative bacilli stands out among multidrug-resistant bacteria mostly due to the production of carbapenemase enzymes which lead to resistance to most β-lactam antibiotics including the carbapenems. As a consequence, polymyxins have been reintroduced in the clinic as a last resort to treat infections caused by Gram-negative bacilli resistant to carbapenems. However, the only reliable method to evaluate the susceptibility to polymyxins is the broth microdilution, a laborious and time-consuming technique. Among infections caused by multidrug-resistant bacteria, bloodstream infections are the most worrisome as they can lead to sepsis and septic shock with high mortality rates. Objective Considering the severity of sepsis and the need for a treatment guided for the susceptibility test in vitro, this work aimed to evaluate a rapid method of polymyxins susceptibility either from colonies grown on agar or directly from positive blood culture bottles using the technology of MALDI-TOF. Methods The method was based on the “direct on target microdroplets growth assay” (DOT-MGA) originally developed by Idelevich and collaborators with some modifications (Adapted DOT-MGA). Isolates of Enterobacterales and non-fermenting Gram-negative bacilli resistant to carbapenems were obtained from patients attending a tertiary care hospital in southern Brazil and tested as follows: 122 isolates from colonies grown on agar plates and 117 isolates directly from spiked positive blood cultures. Results The adapted DOT-MGA presented 95 and 100% of categorical agreement considering the colonies grown on agar plates and directly from positive blood cultures, respectively. Discussion The adapted DOT-MGA test proved to be a reliable technique to evaluate the susceptibility to polymyxins to be used in microbiology laboratories with the MALDI-TOF equipment.